The nature of epistemic feelings (2014)
ABSTRACT: Among the phenomena that make up the mind, cognitive psychologists and philosophers have postulated a puzzling one that they have called ‘‘epistemic feelings.’’ This paper aims to (1) characterize these experiences according to their intentional content and phenomenal character, and (2) describe the nature of these mental states as nonconceptual in the cases of animals and infants, and as conceptual mental states in the case of adult human beings. Finally, (3) the paper will contrast three accounts of the causes and mechanisms of epistemic feelings: the doxastic account; the mental scanner account; and the heuristic mechanism account. The paper will argue in favor of the heuristic mechanism account.